ADVANCING GENDER EQUALITY THROUGH ORGANIZATIONAL TRANSFORMATION: THE CASE OF DHARMA WANITA PERSATUAN (DWP) AND ITS STRATEGIC FUTURE - Sriwardiningsih, Enggal (Bina Nusantara University, 2025)
This study examines the organization of Dharma Wanita Persatuan (DWP) into a strategic platform for advancing gender equality and community empowerment in Indonesia. DWP, comprised of wives of civil servants and female professionals, plays a unique role in promoting women’s participation in the public sphere and leadership. The study focuses on DWP’s periodic development targets and assesses its progress in fostering gender-inclusive and responsive practices. A mixed methods approach is used, combining trend analysis, policy evaluation, and sentiment mapping to assess participation levels, leadership dynamics, and program effectiveness. The findings showed while DWP has initiated some progressive programmes, its hierarchical structure and mandatory membership continue to limit broader engagement. Leadership influence, communication gaps and traditional gender norms are identified as key barriers to transformation. However, there is growing potential to reposition DWP as an inclusive and forward-looking organisation by strengthening digital engagement, leadership training and feedback mechanisms. The study concludes that removing structural barriers and embracing innovation are essential for sustainable change. It offers practical recommendations for policymakers and academics seeking to reform similar gender-based institutions. Ultimately, this research contributes to the discourse on organizational development and gender equality.